The Palgrave international handbook of gender and the military - Woodward, Rachel; Duncanson, Claire (Palgrave Macmillan, 2017)
This 'Handbook' includes coverage of conceptual approaches to the study of gender and militaries, gender and the organisation of state military forces, gender as it pertains to military forces in action, transitions and transgressions within militaries, gender and non-state military forces, and gender in representations of military personnel and practices.